Interpreting Scripture: Essays on the Bible and Hermeneutics - Wright, N. T. (SPCK, 2020)
Intro -- 1 Introduction to The Language and Imagery of the Bible by G. B. Caird -- 2 The Lord's Prayer as a Paradigm of Christian Prayer -- 3 God and Caesar, Then and Now -- 4 Christian Origins and the Question of God -- 5 Faith, Virtue, Justification, and the Journey to Freedom -- 6 Neither Anarchy nor Tyranny: Government and the New Testament -- 7 The Bishop and Living under Scripture -- 8 Imagining the Kingdom: Mission and Theology in Early Christianity -- 9 Revelation and Christian Hope: Political Implications of the Revelation to John -- 10 The Monarchs and the Message: Reflections on Bible Translation from the Sixteenth to the Twenty-First Century -- 11 Joy: Some New Testament Perspectives and Questions -- 12 Pastoral Theology for Perplexing Topics: Paul and Adiaphora -- 13 Apocalyptic and the Sudden Fulfilment of Divine Promise -- 14 The Bible and Christian Mission -- 15 Wouldn't You Love to Know? Towards a Christian View of Reality -- 16 Sign and Means of New Creation: Public Worship and the Creative Reading of Scripture -- 17 The Powerful Breath of the New Creation -- 18 Sacred Space in the City -- 19 Foreword to The Church and Its Vocation: Lesslie Newbigin's Missionary Ecclesiology by Michael Goheen -- 20 The Honest to God Controversy -- 21 Christ and the Cosmos: Kingdom and Creation in Gospel Perspective -- 22 Get the Story Right and the Models Will Fit: Victory through Substitution in 'Atonement Theology' -- Bibliography -- Acknowledgments -- Index of Ancient Sources -- Index of Modern Authors.